Determinants of Regional Economic Growth Using Panel Data from ASEAN Countries, 2000-2022 - Chelsea Carissa Primastika Malau; Stefani Santoso (JENOVA : Journal of Economics, Finance, Accounting, and Organizational Advancement, 2025)
This study investigates the determinants of regional economic growth across ten ASEAN member countries over the period 2000-2022 using a balanced panel data approach. The primary objective is to examine how Foreign Direct Investment (FDI), trade openness, government expenditure, inflation, gross fixed capital formation (GFCF), and human capital development influence GDP per capita growth in the ASEAN region. The study employs three panel data estimation techniques, Pooled Ordinary Least Squares (Pooled OLS), Fixed Effects Model (FEM), and Random Effects Model (REM), followed by the Hausman specification test to select the most appropriate model. Robustness checks are conducted using the Generalized Method of Moments (GMM) estimator to address potential endogeneity concerns. The Hausman test results favor the Fixed Effects Model as the best-fit specification. Empirical findings reveal that FDI, trade openness, GFCF, and human capital exert a statistically significant positive effect on GDP per capita growth, while inflation demonstrates a significant negative relationship. Government expenditure shows a positive but statistically insignificant coefficient across most specifications. The GMM estimation corroborates these findings, confirming the robustness of the results. This study contributes to the literature by providing a comprehensive, multi-variable analysis of economic growth determinants in the ASEAN context with an extended time horizon, offering policy recommendations for enhancing regional economic integration and sustainable development.